Comunicação organizacional e gestão do conhecimento: práticas, interface e modelagem - Ariane Barbosa Lemos (2018)
This study describes and analyzes practices and managerial approaches to organizational communication (OC) and knowledge management (KM) in a company in the car rental services and products sector. In the company, a descriptive and organizational case study was carried out, emphasizing knowledge management initiatives aimed at the socialization of corporate experiences and the internalization of knowledge. The data obtained through interviews with nine company professionals were transcribed and grouped into analysis categories. Based on the study, an integrated model of the areas of OC and KM was proposed, which recognizes the relevance of organizational communication in information sharing and knowledge creation. The proposed modeling refers to the relational paradigm of communication as the most appropriate for the promotion of interpersonal dialogue in the work environment. The model elaborated from the literature review was adapted to the characteristics of the organization participating in the research. The results confirm the enabling contexts investigated are dialogical organizational spaces in which the sharing of information and the creation of organizational knowledge take place through the exchange of experiences and insights among the collaborators in each of the analyzed programs. Communicative processes are mediators, especially as regards the performance of internal communication, applied with the orientation of promoting commitment to the organization, awareness about changing environment, understanding the evolution of goals and the sense of belonging the organization.